Two-dimensional manganese(II) coordination polymer based on phthalate and pyrazine bridges exhibiting antiferromagnetic properties - Gherco, Olesea; Keene, T; Filippova, Irina; Baca, Svetlana; Decurtins, Silvio (Moldavian Journal of the Physical Sciences, 2011)
Magnetic measurements for the 2D coordination polymer [Mn(Pht)(Pyz)(H2O)2]n (1), in